MEMBANGUN SELF-AWARENESS MELALUI EDUKASI VIRTUAL BAGI SISWA SISWI SEKOLAH DASAR DI KOTA CIREBON - Indrayanti, Iin; Putry, Dessy Ratna (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Self-awareness is predominant for every individual, including current situation in particular, where Covid-19 outbreak has globally hit people. The attitude is also expected to be experienced by every student in all levels. The facts that there are still many students who do not realize the importance of having self-awareness in maintaining and implementing health protocols during learning from home or online learning. Accordingly, Community Service Program (PKM) team from Politeknik Harapan Bersama conducted virtual education. The program was carried out with the aim of introducing and building self-awareness among students at MI Darul Hikam Cirebon in implementing health protocols in everyday life. Storytelling was chosen as the method to develop children's affective (feeling), social, and cognitive (appreciation) aspects to raise the awareness. A total of 100 of 6th grade students and 3 homeroom teachers from the school participated in the agenda. The storytelling began with brainstorming the title and several pictures related to the situation before and during the Covid-19 pandemic. Core activities were dedicated to classically perform the 5M movement (Wear Masks, Wash hands with soap and water, Physical Distancing, Reduce Mobility and Avoid crowd) in bilingual. The enthusiasm was shown by the students in demonstrating the movements several times. They were able to mention sequent 5M movement in good English pronunciation. In addition, the students virtually practiced of washing hands and wearing masks well. This shows that the implementation of Community Service Program (PKM) ran smoothly in accordance with the above aim.